Hadith dalam Hegemoni Fiqh: Membandingkan Sahih Ibn Hibban dengan Sunan Ibn Majah - Rifqi Muhammad Fatkhi (Qur'an and Hadith Academic Society, 2012)
This article discusses the hegemony of fiqh in the organization and reception of kitab hadith. One of its finding is that the formation of al-kutub al-sittah and its reception are mostly to meet the fiqh interest than the interest of hadith codification. This article examines also the argument of Ibn Tahir al-Maqdisi who initiated Sunan Ibn Majah as one of the authoritative standard kitab hadith for Muslims. The thesis of al-Maqdisi is used in this article to compare Sahih ibn Hibban and Sunan ibn Majah. This article argues that kitab hadith of Ibn Hibban is more acceptable to be the standard hadith if we use fiqh criteria